2018
DOI: 10.1038/s41598-018-23822-4
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting epigenetic states of heterochromatin in the different types of mouse pluripotent stem cells

Abstract: Mouse embryonic stem cells (ESCs) and epiblast stem cells (EpiSCs) represent naive and primed pluripotency states, respectively, and are maintained in vitro by specific signalling pathways. Furthermore, ESCs cultured in serum-free medium with two kinase inhibitors (2i-ESCs) are thought to be the ground naïve pluripotent state. Here, we present a comparative study of the epigenetic and transcriptional states of pericentromeric heterochromatin satellite sequences found in these pluripotent states. We show that 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 66 publications
10
44
2
Order By: Relevance
“…S3A). In the latter conditions, PCH shifts from H3K9me3 to H3K27me3 (Tosolini et al 2018), indicating that the PCH association of Oct4 is independent of the presence of specific heterochromatic marks. Remarkably, Oct4 staining is…”
Section: Resultsmentioning
confidence: 96%
“…S3A). In the latter conditions, PCH shifts from H3K9me3 to H3K27me3 (Tosolini et al 2018), indicating that the PCH association of Oct4 is independent of the presence of specific heterochromatic marks. Remarkably, Oct4 staining is…”
Section: Resultsmentioning
confidence: 96%
“…The classical DAPI-dense condensed HP1-positive, H3K9me3 heterochromatin foci appear to be more diffuse in ESCs (Aoto et al, 2006;, and they increase in number and compaction during differentiation (Fussner et al, 2011;Kobayakawa et al, 2007;Meshorer, 2007; (Figure 3A), suggesting a global rearrangement of centromeres. A direct side-by-side comparison of 2i-grown, serum-grown, and primed EpiSCs shows an increase in H3K9me3 foci from 2i-to serum-grown to EpiSCs and, somewhat unexpectedly, H3K27me3-positive DAPI domains in 2i-grown cells (Tosolini et al, 2018). Especially visible is the redistribution of the heterochromatin protein HP1b from an almost completely diffuse pattern in nuclei of undifferentiated ESCs to the gradual accumulation in heterochromatin foci during differentiation (Mattout et al, 2015) ( Figure 3B).…”
Section: Developmental Cellmentioning
confidence: 92%
“…Interestingly, in the same study, H3K27me2 was found to display the opposite trend, suggesting that H3K27me2 is partially methylated into H3K27me3 during ESC differentiation. In 2i conditions, H3K27me3 is significantly depleted in developmentally regulated genes (Juan et al, 2016;Marks et al, 2012), but by contrast to the promiscuously transcribing serum-grown ESCs (Efroni et al, 2008;Lin et al, 2012;Nie et al, 2012;Percharde et al, 2017), ground-state ESCs do not show permissive transcription (Marks et al, 2012) and do not express satellite repeats (Tosolini et al, 2018) as serum-grown ESCs do (Efroni et al, 2008;Tosolini et al, 2018), suggesting that transcription in 2i-grown ESCs is blocked by means other than H3K27me3, H3K9me3, or DNA methylation.…”
Section: Chromatin Is Globally More Accessible In Pluripotent Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…Our data highlight the need for independent methods to measure chromatin compaction, as our observations challenge previous assumptions that lower levels of DNA methylation in 2i-treated ES cells (29) also results in less compaction. There have been some reports suggesting that the epigenetic marker H3K27me3 may be able to repress parts of the genome and counterbalance lower levels of DNA methylation, at least within some loci of 2i-treated cells (60,61).…”
Section: Resultsmentioning
confidence: 99%